Efforts to Improve Student Learning Achievement in Aqeedah Moral Subjects Through the Contextual Teaching And Learning Approach - Hascita Istiqomah (eL Bidayah: Journal of Islamic Elementary Education, 2020)
This study aims to improve student achievement in Aqeedah Akhlak through the Contextual Teaching and Learning approach. This research is a class action research carried out in two cycles in the first cycle conducted 2 meetings while in the second cycle conducted 1 meeting. Each cycle consists of planning, implementing actions, observing and reflecting. Data on student learning pest obtained through student test results at the end of cycle I and cycle II, the results of learning activities are seen by racing on the guidelines for student activity observation sheets and teacher activities. The indicator of the success of this study is to improve student learning achievement in the subject of aqidah moral through the Contextual Teaching and Learning approach. Seen at an average value of 86.31 with a classical completeness percentage of 89.43%. The application of the Contextual Teaching and Learning approach can improve student achievement in class III MI Assa'adah Labuapi District, West Lombok Regency Academic Year 2017/2018. [Penelitian ini bertujuan untuk meningkatkann prestasi belajar siswa pada mata pelajaran Aqidah Akhlak melalui pendekatan Contextual Teaching and Learning(CTL). Penelitian ini merupakan penelitian tindakan kelas (PTK) yang di laksanakan dalam dua siklus pada siklus I dilakukan 2 pertemuan sedangkan pada siklus II dilakukan 1 pertemuan. Masing-masing siklus terdiri dari tahap perencanaan, pelaksanaan tindakan, observasi dan refleksi. Data pestasi belajar siswa di peroleh melalui hasil tes siswa pada akhir siklus I dan siklus II, hasil aktivitas kegiatan pembelajaran dilihat dengan berpacu pada pedoman lembar observasi aktivitas siswa dan aktivitas guru. Indikator keberhasilan penelitian ini yaitu meningkatkan prestasi belajar siswa pada mata pelajaran aqidah akhlak melalui pendekatan Contextual Teaching and Learning (CTL). Dilihat pada nilai rata-rata 86,31 dengan presentase ketuntasan klasikal yaitu 89,43%.Penerapan pendekatan Contextual Teaching and Learning (CTL) dapat meningkatkan prestasi belajar siswa kelas III MI Assa’adah Kecamatan Labuapi Kabupaten Lombok Barat Tahun Ajaran 2017/2018]